Vehicle Systems and Excipients Used in Minipig Drug Development Studies. (April 2016) - Weaver, Margaret L.; Grossi, Anette Blak; Schützsack, Jorgen; Parish, Joanna; Løgsted, Jeanet; Bøgh, Ingrid Brück; Cameron, David; Harvey, Warren; Festag, Matthias; Downes, Noel; Venturella, Silvana; Schlichtiger, Julia; et al.
Minipigs have been used for dermal drug development studies for decades, and they are currently more frequently considered as the second nonrodent species for pivotal nonclinical studies, in lieu of the dog or nonhuman primate, for compounds delivered via standard systemic routes of administration. Little is known about the tolerability of different excipients in minipigs; sharing knowledge of excipient tolerability and compositions previously used in nonclinical studies may avoid testing of inadequate formulations, thereby contributing to reduced animal usage. This article reviews vehicles employed in the Göttingen ® minipig based on the combined experience from a number of pharmaceutical companies and contract research organizations. The review includes vehicles tolerated for single or multiple dosing by the Göttingen minipig, some of which are not appropriate for administration to other common nonrodent species (e.g., dogs). By presenting these data for dermal, oral, subcutaneous, and intravenous routes of administration, studies to qualify these vehicles in minipigs can be minimized or avoided. Additionally, investigators may more frequently consider using the minipig in place of higher species if the tolerability of a vehicle in the minipig is known.